2002
DOI: 10.1055/s-2002-25291
|View full text |Cite
|
Sign up to set email alerts
|

Novel Three-Channel and Three-Slit Stiffening Tube for Total Colonoscopy

Abstract: The TCTS stiffening tube was as easy to use as the standard stiffening tube, and is considered to be both safe and useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Resection of a lesion is critical for making a histopathological diagnosis and the only method currently available for larger tumors, 3 cm or more in diameter, in the right colon is piecemeal removal with snare wire strangulations (13)(14)(15). Laparoscopic surgery combined with lymph node dissection has been reported to be most suitable for the treatment of larger superficial tumors of the large bowel, including early large bowel cancer (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resection of a lesion is critical for making a histopathological diagnosis and the only method currently available for larger tumors, 3 cm or more in diameter, in the right colon is piecemeal removal with snare wire strangulations (13)(14)(15). Laparoscopic surgery combined with lymph node dissection has been reported to be most suitable for the treatment of larger superficial tumors of the large bowel, including early large bowel cancer (16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…We have already reported various experimental and clinical results on our large bowel EMR technique using two-channel to three-channel outer tubes and needle knives (13)(14)(15). However, we found that it was often difficult to accurately manipulate the forceps to treat a target lesion in the right colon because this region is about 150 cm from the anus.…”
Section: Discussionmentioning
confidence: 99%
“…prove our technique so that large superficial tumors can be safely resected en bloc and so that the resected tissue piece can be collected easily [4,5].…”
Section: Case Reportmentioning
confidence: 99%